2014
DOI: 10.5005/jp-journals-10006-1280
|View full text |Cite
|
Sign up to set email alerts
|

Study of Change in Knowledge and Attitude of Secondary School Teachers toward Adolescent Reproductive Health Education after Training Program in Rural Schools of Wardha District, Maharashtra

Abstract: This study assessed the effect of training program on teachers' knowledge of and attitude toward reproductive health education/ sexuality education (RHE/SE) in five randomly selected rural schools in rural area of Wardha district, Maharashtra, India. All the 40 teachers in the selected were recruited for the study. They (40 teachers) were all given training in RHE/SE for 1 month. Their knowledge and attitude toward RHE/SE were assessed pre-and post-training program. The results show a significant increase in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…In line with previous studies, results demonstrated that the educational intervention increased teachers' knowledge. These studies emphasize the necessity of educational programs, seminars, and courses to upgrade knowledge on child sex education [21]. Other studies on education for teachers at higher levels similarly show that educational interventions enhance the level of knowledge in teachers [1,22].…”
Section: Discussionmentioning
confidence: 84%
“…In line with previous studies, results demonstrated that the educational intervention increased teachers' knowledge. These studies emphasize the necessity of educational programs, seminars, and courses to upgrade knowledge on child sex education [21]. Other studies on education for teachers at higher levels similarly show that educational interventions enhance the level of knowledge in teachers [1,22].…”
Section: Discussionmentioning
confidence: 84%
“…6 Menurut penelitian Acharya dkk, remaja, terutama kelompok remaja awal menghabiskan banyak waktunya di sekolah dan mengidolakan gurunya sebagai panutan. 7 Oleh karena itu guru dapat menjadi konselor terbaik untuk berbagai perubahan fisik dan mental yang terjadi selama periode usia ini. Hasil-hasil kajian lain juga menemukan bahwa guru merupakan sumber informasi utama tentang kesehatan reproduksi setelah teman.…”
Section: Pendahuluanunclassified